Nucleic Acid Prevalence of Zoonotic Babesia in Humans, Animals and Questing Ticks, a Systematic Review and Meta-Analysis - Xiao-Yan Yao; Shao-Qi Yu; Na Tian; Fei Wang; Shi-Zhu Li; Lan-Hua Li (Tropical Medicine and Infectious Disease, 2023)
Background: Zoonotic Babesia infections are an emerging public health threat globally. The geographical distribution, animal reservoirs and tick vectors vary greatly across Babesia species, and estimations of prevalence reported in works within the literature are also quite different. Better prevalence estimates and identification of moderators are needed to understand the global transmission risk of different zoonotic Babesia species, and to provide crucial background information for the diagnosis, treatment and control of zoonotic babesiosis. Methods: We conducted a systematic review and meta-analysis to determine the global nucleic acid prevalence of different zoonotic Babesia species in humans, animals and ticks. Relevant publications were obtained from several electronic databases and grey literature up to December 2021. Articles were included if they were published in English or Chinese and reported the nucleic acid prevalence of zoonotic Babesia species in humans, animals or ticks. The pooled estimates of prevalence were determined using a random effect model. Heterogeneity was investigated using subgroup analyses and random effect meta-regression models. Results: Of 3205 unique studies, 28 were included by the systematic review of zoonotic Babesia for humans, 79 for animals and 104 for ticks. The results showed overall pooled estimates of nucleic acid prevalence for the following: B. microti—1.93% (0.32–4.69%) in humans; B. microti—7.80% (5.25–10.77%), B. divergens—2.12% (0.73–4.08%) and B. venatorum—1.42% (0.30–3.16%) in animals; and B. microti—2.30% (1.59–3.13%), B. divergens—0.16% (0.05–0.32%), and B. venatorum—0.39% (0.26–0.54%) in questing ticks. The type of population, animal reservoir or tick vector, detecting method and continent were moderators possibly associated with heterogeneity, yet the remaining heterogeneity that was not explained was still substantial (all QE p values < 0.05). Conclusions:B. microti is the most prevalent and widely distributed zoonotic Babesia species globally. The wide range of suitable animal reservoirs and potential transmission vectors and high prevalence in animals and ticks may contribute to the worldwide distribution of B. microti. Other zoonotic Babesia species were relatively less prevalent and were reported in quite limited areas.